EnviroPureTech: Sistem Terpadu Inovatif untuk Pengelolaan Air Limbah Berkelanjutan menggunakan Teknologi Plasma, Reverse Osmosis, dan Turbin Listrik Berbasis IoT - Sa Bashkaran Adi Warman; Janu Andeean; Ridho Firmansyah (Prosiding ESEC, 2023)
Indonesia has rich energy resources, including electrical energy. However, the use of conventional power plants has negative impacts, such as increasing pollution and reducing fossil fuel sources. Therefore, alternative solutions such as energy from aquatic resources are important. As an archipelagic country, Indonesia has great potential to develop electricity and clean water supplies. Unfortunately, around 80% of waste water produced in Indonesia is not treated properly and is discharged directly into the waters. This demands sustainable wastewater management. The use of plasma technology, reverse osmosis and IoT-based electrical energy turbines is a solution to improve wastewater management. EnviroPureTech is an innovation that combines plasma technology to remove harmful compounds in wastewater, reverse osmosis to separate dissolved compounds, and IoT-based electrical energy turbines to produce additional energy from wastewater. This research aims to integrate EnviroPureTech in sustainable wastewater management in Indonesia. The research method involves literature study for data collection and design of the necessary tools. The success of creating this tool is important so that testing runs smoothly. It is hoped that the results of this research will contribute to the development of a sustainable wastewater management system, create a clean environment, and support the use of renewable energy sources.